Comprehensive insight into the extract optimization, phytochemical profiling, and biological evaluation of the medicinal plant Nothapodytesfoetida. (July 2022) - Susanna, Deepti; Balakrishnan, Raj Mohan; Ponnan Ettiyappan, Jagadeeshbabu
Abstract: Nothapodytes foetida is an endemic medicinal plant belonging to the family Icacinaceae from the deciduous forests of the Western Ghats. The extract yield, nutritional and phytochemical composition, metabolite profiling of N. foetida leaf extract has been analysed, along with the assessment of its antioxidant, anti-inflammatory, anti-microbial and anti-cancer potentialities. The effect of different extracting solvents and techniques was optimized to obtain maximum extract yield, and ultrasonication-assisted extraction with aqueous methanol as the solvent was chosen. Appreciable amounts of total phenolics (67.59 mg GAE/g DW), total flavonoids (24.75 mg QCE/g DW), and total tannins (55.67 mg GAE/g DW) were detected. FT-IR spectroscopy also confirmed the presence of alcohols, phenols, alkanes, amino acids, carboxylic acids, nitro compounds and amines in the extract. Further, GC-MS analysis detected the presence of 33 volatile compounds that comprised of viminalol, α, β-amyrins, β, γ-sitosterol, 9-methoxy-camptothecin, lupeols, and various di and tri terpenes in significant quantities. 1 H NMR spectra revealed well-resolved signals for flavonoids, amino acids (trp, his, tyr, phe, ala, ile, gly, gln, thr, val) and organic acids. LC-MS analysis of the methanolic N. foetida extract depicted a higher polyphenolic content followed by the ethanolic and aqueous extracts. Additionally, the aqueous methanolic extract of N. foetida exhibited significant in-vitro antioxidant, anti-inflammatory, anti-microbial activity and anti-cancer activity. The overall results of this work ascertain the potency of N. foetida in nutraceutical and biomedical applications. Graphical abstract: Image 1 Highlights: Optimization of extraction techniques for Nothapodytes foetida. Rich phenolic and flavonoid content was established. Metabolite profiling by FT-IR, GC-MS, NMR and LC-MS detected several significant bioactive compounds. Antioxidant, anti-inflammatory, anti-microbial and anti-cancer activities were analysed. N. foetida leaf extracts were identified to have promising nutraceutical and biomedical application.